Teachings on the prayer of the heart in the Greek and Syrian fathers: the significance of body and community - Gather, Jill (Gorgias dissertations, 2010)
The prayer of the heart and its biblical origins -- The prayer of the heart and its Syrian Christian background -- The prayer of the heart and its Greek Christian background -- The early Byzantine synthesis -- Retrospective and prospective